STATISTICAL PROCESS CONTROL APPLIED TO LOSSES OF PLATFORM IN THE INDUSTRIAL TOMATO COMBINE HARVESTING - Silva, Rouverson Pereira da [UNESP]; Voltarelli, Murilo Aparecido [UNESP]; Zerbato, Cristiano [UNESP]; Alves Silva, Vicente Filho [UNESP]; Cassia, Marcelo Tufaile [UNESP]; Tellez, F. A.; Rodriguez, A. M.; Sancho, I. M.; Robinson, M. V.; RuizAltisent, M.; Ballesteros, F. R.; Hernando, ECC (Fundacion General Univ Politecnica Madrid, 2014)
Losses due to mechanized harvesting of industrial tomatoes are not normally surveyed in Brazil, since studies on this topic are scarce, especially when it comes to losses on the cutting platform, which can reach high levels, can reduce productivity the areas. The objective of this study was to evaluate the variability of losses in the cutting platform in mechanical harvesting of industrial tomatoes through statistical process control. The experiment was conducted in the municipality of Miguelopolis - SP, Brazil, with a harvester Co.Ri.Ma SRl, with six cylinders Iveco engine and power of 129 kW, monofilament, with cutting platform with spacing of 1.50 m. The machine operated at 1800 rpm the engine. The cultivar harvested was Heis 9553 with spacing of 1.25 m between rows. The statistical design was randomized, in bands, constituting 32 sampling points. To collect the fruit losses arising from the cutting platform was used a frame of 2 m(2), kicking the harvester at a distance equal to its length. Was used as a tool of statistical process control the control charts for individual values and moving ranges (I-MR), composed of the upper and lower limits of control and average. The fruit losses in the cutting platform showed instability in the process, indicating that there is presence of special causes extrinsic to the operation, which increase the variability of the process and therefore reduce its quality. In this situation it was found that the points for greater vegetable flow in the machine were the points at which the variability reached the highest values. The increased variability of the losses occurs on the platform for most vegetal flow on the cutting mechanism machine.
Keywords: control charts; quality; variability; Solanum lycopersicum